Synthesis Of CoFe2O4 Nanoparticle and Antibacterial Activity Test - Listiyani Purwitasari; Poedji Loekitowati Hariani; Vivi Sisca (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Cobalt ferrite (CoFe₂O₄) is a spinel ferrite-based material known for its excellent magnetic properties and chemical stability, making it as a promising candidate for biomedical applications as well as an antibacterial agent. This study aims to synthesize CoFe₂O₄ nanoparticles by a coprecipitation methode and evaluate their antibacterial activity against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. The synthesized products were characterized by using several instruments includes X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), FTIR spectroscopy and Vibrating Sampel Magnetometer (VSM) in order to determine its crystal structure, particle morphology, functional groups, and magnetic properties. Antibacterial activity was assessed by using the disk diffusion method. The results showed that CoFe₂O₄ nanoparticles were successfully synthesized with nanometer-scale crystallite sizes and exhibited strong ferromagnetic properties. Antibacterial tests demonstrated inhibition zones against the growth of S. aureus and E. coli, indicating that CoFe₂O₄ has potential as an antibacterial agent. The effectiveness of antibacterial activity was influenced by nanoparticle concentration and the type of tested bacteria. This research opens up further opportunities for the development of CoFe₂O₄ applications in health and environmental fields.